The role of regulator of G-Protein Signalling-1 in macrophage function and the development of atherosclerosis - Patel, J; Jyoti Patel-Oxford University (2011)
Chemokine-induced macrophage recruitment into the vascular wall is an early pathological event in the progression of atherosclerosis. Macrophage activation and chemotaxis during cell recruitment are mediated by chemokine ligation of multiple G-protein coupled receptors. The Regulator of G-Protein Signalling-1 (RGS-1) acts to down-regulate the response to sustained chemokine stimulation. Studies in this laboratory have shown Rgs1 is up-regulated in atherosclerotic ApoE-/- mice in association with atherosclerotic plaque progression and published findings have reported that RGS1 is highly expressed in leukocytes. However an in vivo role for RGS-1 in macrophage function or in atherosclerosis has not been investigated. This thesis aimed to address the hypothesis that RGS1 has an important role in atherosclerosis and modulates the inflammatory response by controlling chemokine signalling and macrophage chemotaxis to atherosclerotic plaques. To investigate the role of RGS1 in macrophage function and the development of atherosclerosis, Rgs1-/- mice were characterised on the ApoE-/- background. Flow cytometric analysis of leukocytes in blood, spleen and bone marrow indicated Rgs1-/-ApoE-/- mice had no significant differences in the numbers of monocytes or lymphocytes compared to ApoE-/- mice. Rgs1 was found to be highly expressed in macrophages from ApoE-/- mice compared to B-lymphocytes, where it has a non-redundant role, and other cells involved in plaque formation. Furthermore, Rgs1 is up-regulated with monocyte-macrophage activation by innate stimuli. For the first time, RGS1 was shown to affect chemokine receptor signalling in macrophages in vitro. Rgs1-/-ApoE-/- macrophages showed significantly enhanced chemotaxis to CCL2, CCL3 and CCL5 and impaired homologous desensitisation to the chemokine CCL5 in comparison to ApoE-/- cells. To determine the role of RGS-1 in leukocyte trafficking and atherosclerosis, a detailed atherosclerosis study was carried out. Rgs1-/-ApoE-/- mice had significantly less lesion formation in the aortic roots at 9-weeks and in the aorta at 16-weeks on a chow diet in comparison to ApoE-/- mice. This was accompanied with decreased macrophage content in the aortic root at 9-weeks. To further investigate aortic leukocyte recruitment, an Angiotensin II-induced model of acute vascular inflammation was used. At 9 weeks of age, Rgs1-/-ApoE-/- mice had significantly less aortic CD45+ leukocytes and CD11b+ myeloid cells recruited to the aorta in comparison to ApoE-/- mice. Collectively, these findings identify a new role for RGS-1 in macrophage function and support a role for RGS-1 in leukocyte recruitment and retention in the initial stages of atherosclerotic plaque formation. These results identify RGS1 as a novel target for the treatment of acute vascular inflammation and early atherosclerosis.